ANALISIS PENGAKUAN, PENILAIAN, PENYAJIAN DAN PENGUNGKAPAN ASET BERSEJARAH PADA LAPORAN KEUANGAN ENTITAS PEMERINTAH DAERAH ACEH (STUDI KASUS PADA MASJID RAYA BAITURRAHMAN) - Said Ikhsan Ridha; Hasan Basri (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This study is aimed to describe the recognition of Masjid Raya Baiturrahman, describes the valuation method used to assess the Masjid Raya Baiturrahman, Baiturrahman’s disclosures describing the government's financial report, and analyze the suitability of the accounting standards applicable to accounting applied to Masjid Raya Baiturrahman.This study used primary data and secondary data. The primary data obtained from interviews with informants research that Provincial Finance Department, the Department of Finance and Asset Management, and managers of the Masjid Raya Baiturrahman. Secondary data used is the government's financial statements and other documents relating to the heritage assets.The results showed that until now the government of Aceh has not made recognition of an asset to the Masjid Raya Baiturrahaman, but due to the expenses which are recorded as capital expenditure for the Masjid Raya Baiturrahman then it implies that the government has recognized it as an asset. Futhermore the Masjid Raya Baiturrahman assessment is not carried out, this happens because the government has difficulty in estimating the age and the price of the acquisition of Masjid Raya Baiturrahman. At this stage of the disclosure of the government of Aceh have only been doing disclose expenses incurred, but not yet express Masjid Raya Baiturrahman as an asset in the financial statements of the government. Overall the government has not fully implemented accounting standards existing heritage assets.